Disminución de los factores de riesgo de fragilidad en adultos mayores que ingresan a programa de rehabilitación cardiaca - Tolentino M., José (Revista Hospital Clínico Universidad de Chile, 2010)
Introduction: Fragilty is a term commonly used to describe a condition in older adults with factors that have a high risk of disability and dependency. The most important risk factors of fragility syndrome include decreased physical capacity and muscle strength, so the objective of this research is to determine whether a mixed exercise program can reduce these risk factors. Materials and methods: Fifteen older adults with risk factors for fragility participated in cardiac rehabilitation program for 8 weeks. The training program consisted of supervised aerobic exercise and strength training 3 times per week. Patients were evaluated with a physicalability test (test 6-minute walk) and measurement of muscle strength (quadriceps dynamometry) before and after the training program. Results: There was a significant increase in physical capacity and muscle strength of the participants, an increase in the average yield in the test of 6-minute walk (17.34%, p <0.001) and an increase in quadriceps muscle strength (p <0.001) atthe end of the exercise program. Discussion: A mixed training program significantly decreased in two of the most important risk factors in the syndrome of frailty (decreased physical capacity and muscle strength), which arises physical exercise as a powerful defensive weapon in the struggle against disability and dependence of older adults (prehabilitation).